The Associative Patterns of drug in Modern Dictionary of American Slang Words - Isti’anah, Arina (Universitas Negeri Semarang, 2019)
Slang words have been exercised by people in every day communication, particularly in informal speaking. The understanding of slang word meanings is beneficial for language users to maintain smooth communication with others. One of the alternatives to study word meanings is utilized by semantic analysis. Drug is one of the most common referent of slang words in English. There are many synonymous words referring to drug, yet this paper displayed some of those words. The data were collected in a purposive sample method. The slang words taken as the data were restricted to those which were produced in 1990s and the 2000s. Three key words referring to drug were involved to sort the data: amphetamine or nervous stimulant, ecstasy, and cocaine. The slang words analyzed were focused on the forms of exocentric compounding. There are two main objectives presented in this paper: to figure out what slang words referring to drugs and describe the associative patterns of the words. The data then were analyzed in terms of their associative patterns adopting Mattielo’s theory (2008). The result shows that most of slang words referring to drug have appearance and effect patterns.